2019
DOI: 10.1177/1538574419868863
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Wound Healing Following Revascularization for Chronic Limb-Threatening Ischemia

Abstract: Objectives: After surgical or endovascular revascularization, some ischemic lesions will not heal, while some others will heal at a variable period of time from the intervention, indicating a multifactorial interaction between local and systematic “wound healing–promoting” factors. Our objective was to identify predictors of wound healing following revascularization for chronic limb-threatening ischemia (CLTI). Methods: A literature review was performed to identify published research concerning clinical, bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 60 publications
0
10
0
2
Order By: Relevance
“…This is due to the increasing number of surgeries in the world, as well as domestic and workplace injuries and combat wounds [10][11][12][13][14]. Furthermore, the increase in life expectancy is accompanied by an increase in the prevalence of chronic trophic ulcers of various origin, the healing of which is a clinical problem [15][16][17][18]. The problem of wound healing is especially important in cases when the patients cannot be continuously monitored by clinicians and in cases when there are special requirements for the surgical scar, e.g., in aesthetic surgery [19].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the increasing number of surgeries in the world, as well as domestic and workplace injuries and combat wounds [10][11][12][13][14]. Furthermore, the increase in life expectancy is accompanied by an increase in the prevalence of chronic trophic ulcers of various origin, the healing of which is a clinical problem [15][16][17][18]. The problem of wound healing is especially important in cases when the patients cannot be continuously monitored by clinicians and in cases when there are special requirements for the surgical scar, e.g., in aesthetic surgery [19].…”
Section: Introductionmentioning
confidence: 99%
“…Kawarada et al [8] found that skin perfusion pressure, a physiology-based parameter, was useful in determining when to end endovascular therapy. Moreover, transcutaneous oxygen pressure, near-infrared spectroscopy, wound blushing phenomenon, and vascular flow reserve have all been studied as endovascular therapy outcome measures [9][10][11][12][13][14]. It has been reported that periwound foot temperature is associated with wound status [15].…”
Section: Introductionmentioning
confidence: 99%
“…Моделирование ран. После наркотизации животных (хлоралгидрат 300 мг/кг внутрибрюшинно) на спине крыс выбривали кожу и создавали раны стандартизированного размера 1 -квадратная рана с длиной каждой стороны 11 мм, глубиной примерно 2 мм (до фасции).…”
Section: методикаunclassified
“…Актуальность проблемы заживления ран постоянно нарастает, что связано с ростом распространенности хронических трофических язв [1][2][3], а также увеличением числа хирургических вмешательств и травм [4][5][6]. Независимо от этиологии ран и сопутствующей патологии в процессе их заживления можно выделить ключевые процессы.…”
Section: Introductionunclassified